Profiling women directors on board: a Malaysian scenario / Nurhaiyyu Abdull Hamid - Abdull Hamid, Nurhaiyyu (2013)
This paper explores the profile characteristics of women directors on board and examines the relationship between these characteristics towards the firm performance in Malaysia. Those characteristics include the proportion of women directors on board, age, family relatedness with the firm, interlocking directorship and education level. The firm financial performance is measured by return on assets (ROA). The sample size for this study consists of firms with women directors only. They are 138 public listed companies from customer products and trading or services sector within the period of 2011. The findings indicate no characteristics of women directors on board in Malaysia have significant relationship with the firm performance measured by ROA. This implies that business case for profile characteristics of women directors on board in Malaysia does not support for this sample. Furthermore, this study also found out that the big size firms which are measured by total assets, have the tendency to hire women directors who are more mature, university graduates and have more interlocking directorships. On the other hand, most of the women directors who have family relationship with the firms are most likely do not have any higher education level academic background. This study offers useful information for Malaysian companies, academicians, policymakers and potential women director in considering the qualified women director to be appointed in order to achieve the government objective on having 30% of women directors on boards by 2016.